1979
DOI: 10.1002/pol.1979.180170603
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic degradation of polycaproamide in 40% sulfuric acid solution

Abstract: The influence of polymer‐polymer interactions and ultrasonic parameters on the ultrasonic degradation of polycaproamide in aqueous 40% H2SO4 was investigated. It was found that the rate data for the concentrations studied could be represented well by Ovenall's rate equation. However values of the rate constant chosen to fit Ovenall's equation tend to decrease with increasing concentration of polycaproamide from 0.5 to 2.0 g/100 cm3. With increasing ultrasonic power, the degradation rate increases, but it decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Degradation as well as depolymerisation occurs as a result of elongational flow fields, thus producing a less viscous polymer [22]. The rate of degradation increased with an increase in ultrasonic power [48][49][50].…”
Section: Chemical Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Degradation as well as depolymerisation occurs as a result of elongational flow fields, thus producing a less viscous polymer [22]. The rate of degradation increased with an increase in ultrasonic power [48][49][50].…”
Section: Chemical Effectsmentioning
confidence: 99%
“…The effects of ultrasonic power on degradation of hydroxyethyl cellulose and poly (ethylene oxide) in aqueous solutions [49,50,52] were investigated. They reported that the efficiency and rate of degradation process increased with an increase in ultrasonic power.…”
Section: Chemical Effectsmentioning
confidence: 99%